1996
DOI: 10.1001/archinte.1996.00440060067008
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes of Acute Medical Illness and Hospitalization in Older Persons

Abstract: This study documents a high incidence of functional decline after hospitalization for acute medial illness. Although there are several potential explanations for these findings, this study suggests a need to reexamine current inpatient and postdischarge practices that might influence the functioning of older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
275
3
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 499 publications
(290 citation statements)
references
References 26 publications
7
275
3
5
Order By: Relevance
“…This could bias the results in either direction: acutely ill patients could overestimate the presence of symptoms and functional limitations before the onset of illness or underestimate these symptoms and limitations. However, previous studies have demonstrated the validity of retrospective reports for assessing functional status before admission to hospital in acutely ill patients 34 35. Finally, one needs to be appropriately cautious in the interpretation of our study findings because of the relatively small number of post-discharge deaths.…”
Section: Discussionmentioning
confidence: 84%
“…This could bias the results in either direction: acutely ill patients could overestimate the presence of symptoms and functional limitations before the onset of illness or underestimate these symptoms and limitations. However, previous studies have demonstrated the validity of retrospective reports for assessing functional status before admission to hospital in acutely ill patients 34 35. Finally, one needs to be appropriately cautious in the interpretation of our study findings because of the relatively small number of post-discharge deaths.…”
Section: Discussionmentioning
confidence: 84%
“…Between 25% and 50% of older people who are hospitalised lose some of their functional abilities during their hospital stay (Inouye et al 1993). Furthermore, three months after a hospitalisation, 66% have not regained their previous level of functioning (Boyd et al 2009a, Sager et al 1996, Sager and Rudberg 1998.…”
Section: The Role Of Home Care In Supporting Older Peoplementioning
confidence: 99%
“…It is estimated that one-third of older community-living people do not recover their usual activities of daily living (ADL) independence by the time of discharge. 41,42 In a French multicenter survey, hospital-acquired loss of autonomy in older patients was independently predicted by pre-admission walking difficulties, lack of autonomy, risk of falling, and malnutrition risk. 43 The effects of diabetes have not been tested, but the older patient with T2DM has a higher risk of walking limitations and a history of falling 40 and should be considered at risk for hospital-acquired loss of autonomy.…”
Section: Prevention Of Functional Loss In Hospital and Loss Of Autonomentioning
confidence: 99%